政府与人民记忆方式的差异 ：新加坡旧福特车厂的保留过程 = The differing act of remembrance by the government and its people : preservation of Singapore former Ford factory - 曹惠玲 Cho, Caroline Wai Leng (2019)
1942年 2月 15日，英军在福特汽车厂 (Ford Motor Factory) 签署投降协议书，正式把新加坡转交给日军。这一刻历史性的权力交接过程，使新加坡历经了长达三年八个月的殖民地生活。时隔数年，秉持着“向前看”的思想，新加坡政府开始深入的挖掘和重新认识具有历史和文化意义的建筑物，这个时期涌起了一股纪念二战的热潮，旧福特汽车厂在时代的推动下，被政府列为国家古迹奠定车厂在新加坡二战历史史迹的重要位置。本文将借用空间理论，通过旧福特汽车厂所代表的历史记忆和文化资源，挖掘空间在时代的变化中意义的产生和再生成的过程，结合新加坡政府和人民对旧福特车厂保留过程的态度以及协商过程，比较政府和民间记忆的方式的差异。On 1942, February 15, the British Colonial Masters signed the surrender documents and officially relinquished control of Singapore at Ford Motor Factory. This fateful day marked the start of Japanese reign of terror over Singapore. As time passed, Singapore became independent under a local government who constantly pride itself of progressive values. Despite it’s forward looking stance, there was a reorientation to find value in the past, to actively preserve old architectures of historical and cultural significance and an active commemoration of World War Two events. During this period, Old Ford Factory’s historical significance resurfaced and was gazetted as a national monument. Using spatial theories, this thesis aims to treat Old Ford Factory as a space capable of producing and reproducing meaning, defined by the socio-economic conditions of different times, and define and survey the Old Ford Factory as a historical memory and cultural resource significant to the contemporary needs of Singapore today, by the act of remembrance made by the government and its people through negotiation on its preservation process.